A search for genetic factors influencing immune responses to a killed Mycobacterium avium subspecies paratuberculosis vaccine in Australian fine-wool merino sheep : thesis in fulfilment of the degree of Doctor of Philosophy in Animal Science, Institute of Veterinary, Animal and Biomedical Sciences, College of Sciences, Massey University - Dukkipati, Venkata Sayoji Rao (Massey University, 2007)
VSR Dukkipati (2007). A search for genetic factors influencing immune responses to Mycobacterium avium subspecies paratuberculosis. Doctoral thesis, Massey University, Palmerston North, New Zealand. A study was conducted to identify associations between genetic markers and immune responses in Australian fine-wool Merino sheep to a killed Mycobacterium avium subspecies paratuberculosis (Map) vaccine (GudairTM). Blood samples and immune response data (antibody and interferon gamma, IFN-gamma results) were obtained from 934 sheep from a longterm Map vaccination trial undertaken on three independent properties in New South Wales, Australia. Blood samples were genotyped for eight microsatellite markers that included four (DYMS1, OLADRW, OLADRB and SMHCC1) from the Ovar-Mhc region, two each from the SLC11A1 (OVINRA1 and OVINRA2) and IFN-gamma (o(IFN)gamma and OarKP6) gene regions. Vaccination with GudairTM induced strong antibody and IFN-gamma responses as early as two weeks post-vaccination. Between-property differences in magnitude and trend of immune responses, concomitant with season of vaccination and magnitude of natural infection prevalent in individual flocks, were evident. Immune responses in controls on all the three properties remained consistently low, except for slightly elevated IFN-gamma levels at a few time points in controls of properties 2 and 3, concomitant with exposure to natural infection. There were only 2 alleles and 3 genotypes for marker o(IFN)gamma but other loci exhibited extensive polymorphisms, the most occurring at OLADRW which had 42 alleles and 137 genotypes. Heterozygosities varied between 33% (OVINRA2) and 87% (SMHCC1), while polymorphic information contents ranged from 0.31 (o(IFN)gamma) to 0.88 (OLADRW). Genotypes at loci DYMS1, OLADRB, SMHCC1, OVINRA1 and o(IFN)gamma were in Hardy- Weinberg equilibrium (HWE), while those at OarKP6 were in HWE only when rare alleles (<1.0% frequency) were pooled with the closest size class. Departure from HWE, resulting from possible preferential amplification of alleles in heterozygotes, was evident at OLADRW and OVINRA2. Associations between immune responses and genetic polymorphisms at the marker loci were examined by analysing both genotypic and allelic affects. The study revealed several genotypes/alleles at different marker loci to be significantly associated with antibody and IFN-gamma responses to vaccination with GudairTM. However, the majority of those effects were inconsistent across the three properties. Based on significance and consistency in effects across the three properties, five genotypes (two at DYMS1 and one each at OLADRB, SMHCC1 and OVINRA1) and three alleles (one each at DYMS1, OLADRB and o(IFN)gamma) were considered either ‘probable’ or ‘most likely’ to be associated with low IFN-gamma responses, while a genotype at o(IFN)gamma was considered ‘most likely’ to influence high IFN-gamma responses. An allele at OarKP6 was considered ‘probable’ to be associated with low antibody responses to vaccination. Considering the significance of IFN-gamma responses in protection against Map, it is likely that the identified genotype/alleles influencing IFN-gamma responses to vaccination would also influence immune responses to natural Map infections. However, further studies need to be conducted to determine the role of these marker genotypes/alleles in protection against paratuberculosis under natural infection conditions. Key words: paratuberculosis, OJD, Johne’s disease, sheep, immune response, genetic markers, gene polymorphisms, MHC, SLC11A1, IFN-gamma
Keywords: Immunology; Merino sheep; Paratuberculosis; Johne's disease; Immune response; Genetic markers; Gene polymorphisms; IFN-gamma; Fields of Research::300000 Agricultural, Veterinary and Environmental Sciences::300500 Veterinary Medicine::300504 Immunology